The Effect of Coworker Support and Work Motivation on Employee Performance Through Job Satisfaction as an Mediating Variable - Pratama, M. Emeraldo; Yulasmi, Yulasmi; Lusiana, Lusiana (UPI YPTK Journal of Business and Economics, 2024)
Research with the title "The Effect of Colleague Support and Work Motivation on Employee Performance through Job Satisfaction as an Intervening Variable in Employees of the Population and Civil Registration Service of Sungai Banyak City". The object of this research is employees of the Population and Civil Registration Service of Sungai Banyak City. The type of research used used in this research is quantitative causality research, the data collection method is by distributing questionnaires. The analysis technique used is multiple linear regression analysis with the help of the smartPLS program. The sampling technique in this research used a saturated sample by analyzing 74 respondents.  Based on the results of the analysis, it can be concluded that co-worker support has a positive and significant effect on job satisfaction. Work motivation has a positive and significant effect on job satisfaction. Colleague support has a positive and significant effect on employee performance. Work motivation has a positive and significant effect on employee performance. Job satisfaction has a positive and significant effect on employee performance. Job satisfaction does not mediate the effect of coworker support on employee performance. Job satisfaction mediates the influence of work motivation on employee performance.